Current Antimicrobial-resistant Prevalence by Hospital Characteristics: Analysis of Microbiological Data from October 2016 to March 2017 in 339 US Hospitals. (4th October 2017) - Tabak, Ying; Gupta, Vikas; Johannes, Richard; Kurtz, Stephen; Murray, John; Murray, Patrick
Abstract: Background: Antimicrobial resistance (AMR) infections are serious threats. Most current data provide timely actionable information for patient care and public health. Methods: Using an electronic research database from Becton, Dickinson & Company, we analyzed microbiological data from October 2016 to March 2017. We used the CDC definitions to identify 7 important types of non-duplicate AMR pathogen events (first isolate of a species per 30 day period): (1) Methicillin-resistant S . A ureus (MRSA), (2) extended-spectrum β-lactamases (ESBL), (3) multidrug-resistant Enterobacteriaceae (MDR-ENT), (4) Carbapenem-resistant Gram-negative rods (CarbR-GN), (5) Vancomycin-resistant Enterococci (VRE) 6) MDR P . aeruginosa (PsA), and (7) MDR A.  baumannii (ACB). We compared AMR event rates per 100 admissions by geographic region, bed size, teaching, and urban status using weighted χ 2  test. Results: Hospital characteristics were: 38% vs. 62% (teaching vs. non-teaching); 24% vs. 76% (rural vs. urban); 22%, 40%, and 38% (small, medium, and large); and 9%, 46%, 30%, and 15% (Northeast, South, Midwest, and West), respectively. Across 2, 554, 812 admissions, 356, 125 non-duplicate isolates were tested and 53, 981 AMR pathogen events identified: 41% MRSA, 18% ESBL, 13% MDR-ETN, 11% CarbR-GN, 10% VRE, 5% MDR PsA, and 1% ACB. The AMR rates per 100 admissions were higher in teaching and large hospitals for the overall (2.38% vs. 1.81%, teaching vs. non-teaching; 2.28%, 1.82%, and 1.78% for large, medium, and small) and across all AMR subcategories (all P < 0.0001). Northeast showed higher overall AMR rates than other regions and for all subcategories (all P < 0.001), except for MDR PsA and ACB. Conclusion: Teaching and larger hospitals have higher observed AMR event rates per 100 admissions across all AMR subcategories analyzed. Northeast region also showed higher AMR rates for the majority of the AMR pathogen subcategories. Disclosures: Y. Tabak, Becton Dickinson and Company: Board Member, Salary. R. Johannes, BD: Employee, Salary. S. Kurtz, Becton Dickinson and Company: Employee, Salary. P. Murray, Becton, Dickinson and Company: Employee, Salary